FLAMMABILITY OF ORNAMENTAL SPECIES FOR FIRE MANAGEMENT IN WILDLAND-URBAN INTERFACE IN PARANÁ STATE - Batista, Antonio Carlos; Biondi, Daniela; Martini, Angeline (Floresta, 2020)
The objective of this work was to evaluate the flammability of ornamental species as a tool for fire management in areas of wildland-urban interface in Paraná. For this, native ornamental species and exotic species were selected. Initially, the following morphological characteristics of the leaves, which are associated with the flammability of the selected species were evaluated: texture, exudates, hairiness and enervation. The flammability characteristics of the species were analyzed through burning experiments. Fifty 1g burns of freshly harvested plant material of each species were conducted in an epiradiator. The variables collected were: ignition frequency (FI), time to ignition (TI), combustion duration (DC) and combustion index (CI). These variables were statistically analyzed by the SNK test at 95% probability. The Cluster test was also performed to identify different levels of flammability of the species tested as a function of the morphological characteristics and the flammability parameters obtained in the epiradiator tests. The results showed that FI and TI were lower in most native species (except Verbena rigida), differing statistically from exotic ones. There were differences among the species as a function of the species leaf morphology and the flammability parameters measured during the burning. It can be inferred that most native species may have been considered slightly flammable and exotic as flammable, with the exception of the species Euonymus japonica, classified as zero flammability, concluding that native species are the most suitable for use in fire management in wildland-urban interface areas in Paraná, and should be intensively used in landscaping.